2003
DOI: 10.1097/01.ju.0000049032.38743.c7
|View full text |Cite
|
Sign up to set email alerts
|

Disease Progression and Survival of Patients With Positive Lymph Nodes After Radical Prostatectomy. Is there a Chance of Cure?

Abstract: Meticulous lymph node dissection reveals a high rate of metastases (25%). In patients with positive nodes time to progression is significantly correlated with the number of diseased nodes. Some patients with minimal metastatic disease remain free of prostate specific antigen relapse for more than 10 years after prostatectomy without any adjuvant treatment. Meticulous pelvic lymph node dissection, particularly in patients with micrometastases, seems not only to be a staging procedure, but may also have a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
268
4
16

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 401 publications
(304 citation statements)
references
References 24 publications
16
268
4
16
Order By: Relevance
“…However, it has been long understood that degree of LN involvement has a significant role in outcome. Whether microscopic versus gross involvement [4,5], LN tumor volume [6], presence of extracapsular extension [7] or described by ratio [5,8,9], less LN involvement contributes to longer survival than more involvement.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been long understood that degree of LN involvement has a significant role in outcome. Whether microscopic versus gross involvement [4,5], LN tumor volume [6], presence of extracapsular extension [7] or described by ratio [5,8,9], less LN involvement contributes to longer survival than more involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Bader et al reported a 5 year CSS of 90% if only one lymph node was invaded. 43 Schumacher et al showed a 10 year cancer specific survival (CSS) of 78,6% if maximum 2 lymph nodes were involved. 44 Patients with minimal LNI might thus not be incurable and one might question whether 9 adding adjuvant whole pelvic EBRT to the postoperative setting might further improve local control and might prevent metastatic disease and PC death.…”
Section: Whole Pelvis Irradiation For Lymph Node Metastasized Pcmentioning
confidence: 99%
“…In addition, a therapeutic and cancer-specific survival benefit may occur after PLND. [1][2][3][4] With the rise of the prostate-specific antigen (PSA) era, a downward stage migration resulting from the earlier detection of prostate cancer has led to a decreased incidence of positive LNs. [20][21][22] To determine who should undergo a PLND, the benefits must be weighed against the associated comorbidities and applied to those who are at risk of metastatic disease.…”
Section: Who Should Undergo Plnd?mentioning
confidence: 99%
“…Similarly, in another small series, 42 patients with low tumor bulk and one positive LN had survival rates comparable to those matched controls at 5-year follow-up. Recently, Bader et al 1 demonstrated the probability of PSA relapse, symptomatic progression and tumor-related death increased with each additional positive LN removed. They performed a careful extended PLND and RRP on 367 men with clinically organ-confined prostate cancer; 92 (25%) had positive LNs.…”
Section: Are There Therapeutic Benefits To Performing Plnd?mentioning
confidence: 99%
See 1 more Smart Citation